Integrated Strategic Planning of Global Production Networks and Financial Hedging under Uncertain Demands and Exchange Rates - Achim Koberstein; Elmar Lukas; Marc Naumann (BuR - Business Research, 2013)
In this paper, we present a multi-stage stochastic programming model that integrates financial hedging decisions into the planning of strategic production networks under uncertain exchange rates and product demands. This model considers the expenses of production plants and the revenues of markets in different currency areas. Financial portfolio planning decisions for two types of financial instruments, forward contracts and options, are represented explicitly by multi-period decision variables and a multi-stage scenario tree. Using an illustrative example, we analyze the impact of exchange-rate and demand volatility, the level of investment expenses and interest rate spreads on capacity location and dimensioning decisions. In particular, we show that, in the illustrative example, the exchange-rate uncertainty cannot be completely eliminated by financial hedging in the presence of demand uncertainty. In this situation, we find that the integrated model can result in better strategic planning decisions for a risk-averse decision maker compared to traditional modeling approaches.
urn:nbn:de:0009-20-38110
Keywords: 650; financial hedging; stochastic programming; strategic production network planning; uncertainty